Quorum Sensing Activity of Enterobacter asburiae Isolated from Lettuce Leaves - Kok-Gan Chan; Jian Woon Chen; Wai-Fong Yin; Yin Yin Lau; Joanita Sulaiman (Sensors, 2013)
Bacterial communication or quorum sensing (QS) is achieved via sensing of QS signaling molecules consisting of oligopeptides in Gram-positive bacteria and N-acyl homoserine lactones (AHL) in most Gram-negative bacteria. In this study, Enterobacteriaceae isolates from Batavia lettuce were screened for AHL production. Enterobacter asburiae, identified by matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF-MS) was found to produce short chain AHLs. High resolution triple quadrupole liquid chromatography mass spectrometry (LC/MS) analysis of the E. asburiae spent supernatant confirmed the production of N-butanoyl homoserine lactone (C4-HSL) and N–hexanoyl homoserine lactone (C6-HSL). To the best of our knowledge, this is the first report of AHL production by E. asburiae.